Sistem Pendukung Keputusan Seleksi Penerima Bantuan Sosial Menggunakan Metode Simple Additive Weighting - Sitanayah, Lanny; Kansil, Rayuni A.F; Kumenap, Vivie D (Program Studi Teknik Informatika, 2024)
Social assistance is a program or provision of funds organized by the government or non-government to help individuals, families or community groups in need. The government allocates social assistance funds to protect society from possible social risks, increase economic capacity and/or social welfare. In Kelurahan Bebali Siau Timur, the distribution of social assistance has been implemented since 2011 in the form of assistance for family economic welfare (clothing and food). The distribution of social assistance is carried out by registering data on every family registered in Kelurahan Bebali, namely 325 heads of families. The large amount of data on families receiving social assistance with quite a lot of criteria makes employees in the selection section for receiving social assistance less efficient in inputting the existing data. This research aims to help selection employees for receiving social assistance in selecting families who are worthy of receiving social assistance and increasing efficiency in inputting existing data by building a Decision Support System for Selection of Social Assistance Recipients Using the Simple Additive Weighting Method. It is hoped that this system can help in selection and increase the efficiency of data entry. Based on the results of the tests that have been carried out, the Decision Support System for Selection of Social Assistance Recipients Using the Simple Additive Weighting Method can help selection employees in selecting and increasing the efficiency of data input.